2018
DOI: 10.1051/epjconf/201817513008
|View full text |Cite
|
Sign up to set email alerts
|

BsKℓv form factors with 2+1 flavors

Abstract: Using the MILC 2+1 flavor asqtad quark action ensembles, we are calculating the form factors f 0 and f + for the semileptonic B s → Kℓν decay. A total of six ensembles with lattice spacing from ≈ 0.12 to 0.06 fm are being used. At the coarsest and finest lattice spacings, the light quark mass m ′ l is one-tenth the strange quark mass m ′ s . At the intermediate lattice spacing, the ratio m ′ l /m ′ s ranges from 0.05 to 0.2. The valence b quark is treated using the Sheikholeslami-Wohlert Wilson-clover action w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…HPQCD has recently emphasized the value of form factor ratios for the processes B s → Kℓν and B s → D s ℓν for determination of |V ub /V cb | [584]. Preliminary results from FNAL/MILC have been reported for N f = 2 + 1 [585] and N f = 2 + 1 + 1 [581]. Archival papers are expected soon.…”
Section: Form Factors For B S → Kℓνmentioning
confidence: 99%

FLAG Review 2019

Aoki,
Aoki,
Becirevic
et al. 2019
Preprint
Self Cite
“…HPQCD has recently emphasized the value of form factor ratios for the processes B s → Kℓν and B s → D s ℓν for determination of |V ub /V cb | [584]. Preliminary results from FNAL/MILC have been reported for N f = 2 + 1 [585] and N f = 2 + 1 + 1 [581]. Archival papers are expected soon.…”
Section: Form Factors For B S → Kℓνmentioning
confidence: 99%

FLAG Review 2019

Aoki,
Aoki,
Becirevic
et al. 2019
Preprint
Self Cite
“…At this conference, there have been presentations on the heavy-to-light form factor calculations by Fermilab/MILC (Gelzer et al [38], see also [39,40] for preliminary results at Lattice 2017), RBC/UKQCD (Witzel et al [41]), JLQCD (Colquhoun et al [42], see also [43]), HPQCD (Bouchard et al [44], see also [45] for a full paper), as well as ETM (Riggio et al [46], see also [47] for a full paper).…”
Section: Heavy-to-light Decaysmentioning
confidence: 99%
“…Preliminary reports on this study can be found in Refs. [37,38], where the vector current renormalization factors were still multiplied by a blinding factor. This factor was disclosed only after the analysis was finalized.…”
Section: Introductionmentioning
confidence: 99%